The Effectiveness of Whatsapp Social Media Use As A Public Communication Means In Tune Village, Tobu District, Tts District - Made N.D. ANDAYANA; Primus LAKE; Catryn V. ADAM; Aspri Budi OKTAVIANTO; Andreas A. PENI (PT Keberlanjutan Strategis Indonesia, 2023)
Tune Village, Tobu District, South Central Timor District has utilized the WhatsApp social media to communicate with the village community. The village government provides an opportunity for all communities to join as members with the aim that all public information can be disseminated quickly and accurately. This research is a descriptive research with a qualitative approach. The data in this study obtained through primary and secondary sources with a total of 39 informants. The data that has been collected by interview, observation and document search methods is then analyzed using the spiral data analysis technique proposed by Creswell (2016: 264-268). The research results found that; (1) The use of communication media through the Tune Information Whatsapp group is very helpful to the residents and the Tune Village Government in that information can be conveyed quickly and easily; (2) Access to the use of communication media through the Whatsapp Tune Information group is not maximized, because not all Tune Village residents have mobile devices; (3) Utilization of communication media through the Whatsapp Tune Information group is not limited as a medium of communication, but also as a medium of discussion for Tune Village residents; (4) Utilization of communication media through the Tune Information Whatsapp group can improve the welfare of Tune Village residents because residents get information about the use of social media and online shops as a medium for selling handicraft products and disseminating information about Tune Village to deserving audiences about the cultural festival being held in Tune Village.